2008
DOI: 10.1155/2008/783036
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Chromium Ion by Acid Activated Low Cost Carbon‐Kinetic, Mechanistic, Thermodynamic and Equilibrium Studies

Abstract: A carbonaceous adsorbent prepared from an indigenous waste by acid treatment was tested for its efficiency in removing chromium ion. The parameters studied include agitation time, initial chromium ion concentration, carbon dose, pH and temperature. The adsorption followed first order reaction equation and the rate is mainly controlled by intra-particle diffusion. Freundlich and Langmuir isotherm models were applied to the equilibrium data. The adsorption capacity (Qm) obtained from the Langmuir isotherm plots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 6 publications
1
20
0
1
Order By: Relevance
“…8). The value of R L (0.007) was observed to be in the range of 0 to 1, which confirms that the adsorption process was favorable (Arivoli et al, 2008).…”
Section: Adsorption Isothermssupporting
confidence: 52%
“…8). The value of R L (0.007) was observed to be in the range of 0 to 1, which confirms that the adsorption process was favorable (Arivoli et al, 2008).…”
Section: Adsorption Isothermssupporting
confidence: 52%
“…The values of id and can be determined from the slope and intercept of the plot versus 1/2 and are listed in Table 3 ( Figure 6). Values of give an idea about the thickness of boundary layer; that is, the larger the intercept, the greater the contribution of the surface sorption in the rate controlling step [35]. Based on this plot (Figure 6), it was concluded that the sorption process of Cr(VI) is comprised of two phases, suggesting that intraparticle diffusion mechanism is not the rate limiting step for the whole reaction.…”
Section: Intraparticle Diffusionmentioning
confidence: 95%
“…They also reported that as 1/n tends to zero, surface of adsorbent becomes more heterogeneous the influence of the ions on the surface of the adsorbent, making it more heterogeneous. Values of n obtained for all metal Arivoli et al (2005) reported that adsorption intensity (n) > 1 indicates the prevalence of chemisorptions over physical adsorption. K F value obtained for Fe (9.484 mg/g) for is greater than that of Pb (7.311mg/g).…”
Section: Intra-particle Diffusionmentioning
confidence: 99%